Metalloproteinases and their Inhibitors under the Course of Immunostimulation by CPG-ODN and Specific Antigen Inhalation in Equine Asthma. (17th June 2019) - Barton, Ann Kristin; Shety, Tarek; Klier, John; Geis, Sabine; Einspanier, Ralf; Gehlen, Heidrun
Abstract : Objectives . Inhalation of immunostimulatory bacterial DNA segments (cytosine-phosphate-guanosine-oligodeoxynucleotides, CpG-ODN) normalizes clinical and cytologic parameters in severe equine asthma. We hypothesized that CpG-ODN inhalation also reduces the misbalance of elastinolytic activity in asthmatic horses. Methods . Twenty asthmatic horses diagnosed by clinical examinations using a scoring system were included. All horses inhaled CpG-ODNs for 14 days in 2-day intervals. Matrix metalloproteinase (MMP-2/-9) and tissue inhibitors of metalloproteinase (TIMP-1/-2) concentrations were measured in tracheal aspirates using equine sandwich ELISAs before and 2 and 6 weeks after CpG-ODN inhalation. Results . MMP and TIMP concentrations correlated with the results of clinical scoring in all stages of equine asthma. Inhalation therapy led to significant reductions in clinical scores. MMP-2, MMP-9, and TIMP-2 concentrations were significantly reduced immediately, and all MMP and TIMP concentrations 6 weeks after therapy. Discussion . In equine asthma, overexpression of MMPs contributes to pathological tissue destruction, while TIMPs counteract MMPs with overexpression leading to fibrosis formation. The results of this study show that CpG-ODN inhalation may be an effective therapy to address a misbalance in equine asthma. Conclusions . Misbalance of elastinolytic activity seems to improve by CpG-ODN inhalation for at least 6 weeks posttherapy, which may reduce the remodeling of the extracellular matrix. Further studies should evaluate this effect in comparison to glucocorticoid inhalation therapy. Significance . CpG-ODN inhalation may be an effective therapy in the prevention of pulmonary fibrosis formation in equine asthma.